2009
DOI: 10.1038/hdy.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the major chemosensory gene families in insects

Abstract: Chemoreception is a crucial biological process that is essential for the survival of animals. In insects, olfaction allows the organism to recognise volatile cues that allow the detection of food, predators and mates, whereas the sense of taste commonly allows the discrimination of soluble stimulants that elicit feeding behaviours and can also initiate innate sexual and reproductive responses. The most important proteins involved in the recognition of chemical cues comprise moderately sized multigene families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
383
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(410 citation statements)
references
References 71 publications
21
383
4
2
Order By: Relevance
“…Our findings on CSP gene family evolution in ants agree with reports on highly dynamic evolution of animal chemosensory genes by birthand-death model (Nei et al, 2008;Sánchez-Gracia et al, 2009), but depart from those studies that found insect CSPs to be a conserved gene family (Sánchez-Gracia et al, 2009). Earlier studies have shown that many insect CSPs are ancient and shared by different insect orders Gong et al, 2007;Xu et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our findings on CSP gene family evolution in ants agree with reports on highly dynamic evolution of animal chemosensory genes by birthand-death model (Nei et al, 2008;Sánchez-Gracia et al, 2009), but depart from those studies that found insect CSPs to be a conserved gene family (Sánchez-Gracia et al, 2009). Earlier studies have shown that many insect CSPs are ancient and shared by different insect orders Gong et al, 2007;Xu et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…The number of gene copies within a gene family can vary extensively between species and even within a species (Schrider and Hahn, 2010). This copy number variation has been suggested to have a significant role in adaptation and could provide raw material for genes with new functions (Sánchez-Gracia et al, 2009;Innan and Kondrashov, 2010). Rapid turnover of genes within a gene family has been shown to correlate with fast evolution at sequence level (Chen et al, 2010), and gene families which are conserved in size also evolve, on average, more slowly at sequence level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ORs are expressed in the cell membranes of olfactory sensory neurons (OSNs) and are responsible for the detection of odor molecules (Sanchez-Gracia et al, 2009). In general, OSNs will express either ORs or IRs, with the latter mostly tuned to compounds of lower molecular weight (Hallem et al, 2004(Hallem et al, , 2006Benton et al, 2009;Silbering et al, 2011).…”
Section: Introductionmentioning
confidence: 99%